Oral antihistamines for seasonal allergic conjunctivitis - Kamegasawa, Amélia [UNESP]; Chaoul, Mauricio M. [UNESP]; El Dib, Regina [UNESP] (Wiley, 2014)
This is the protocol for a review and there is no abstract. The objectives are as follows: To evaluate the effectiveness and safety of oral antihistamines (such as loratadine, desloratadine, cetirizine, levocetirizine, fexofenadine, terfenadine) in patients with SAC.